The music theory of Godfrey Winham - Blasius, Leslie David, 1955- (Princeton legacy library., 1997)
This book serves as an introduction to the work of Godfrey Winham, an influential figure in American music theory circles in the 1960s. Little published in his lifetime, Winham left behind, at his premature death in 1974, a massive collection of notes: correspondence, unfinished articles, sketches for books, etc. These notes were transcribed and deposited in the Special Collections of Firestone Library at Princeton University. They cover a fascinating range of subjects: exercises in analytical logic, thoughts on the construction of a formally consistent music theory, studies of particular p.